Supreme laryngeal mask airway for cesarean section under general anesthesia: a 10-year retrospective cohort study - Geng, Zhiyu; Li, Chunqing; Kong, Hao; Song, Linlin (Frontiers in Medicine, 2023)
Background Previous research showed the use of supraglottic airways in obstetric anesthesia. The relevant evidence of laryngeal mask airway (LMA) on maternal and neonatal outcomes is still limited. We aimed to assess the maternal and neonatal outcomes when the LMA Supreme was used for cesarean section under general anesthesia. Methods We included all patients who underwent general anesthesia for cesarean section between January 2010 and December 2019. Propensity score matching was used to reduce potential bias from non-random selection of airway intervention. The primary outcome was adverse maternal and neonatal outcomes defined as maternal regurgitation, aspiration, hypoxemia, and low neonatal Apgar scores. Secondary outcomes included patient admission to the intensive care unit, neonate required tracheal intubation, external cardiac massage, and admission to the neonatal intensive care unit. Results A total of 723 patients were included in the analysis; of whom, 221 received Supreme laryngeal mask airway (LMA group) and 502 were intubated with an endotracheal tube (ETT group). After propensity score matching, 189 patients remained in each group. No episode of regurgitation and aspiration occurred in both groups. There was no difference in the rates of Apgar score below 7 at 1 min (14.3% LMA group vs. 15.3% ETT group, OR 0.931, 95% CI 0.574 to 1.510, P = 0.772) and 5 min (3.7% vs. 4.2%, OR 0.875, 95% CI 0.324 to 2.365, P = 0.792). No difference was observed in the secondary outcomes between the two groups. Conclusion The LMA Supreme was not associated with higher adverse maternal and neonatal outcomes when compared to an endotracheal tube for cesarean section under general anesthesia. It might be considered an alternative to tracheal intubation in obstetric practice.